Preschool and School Phases of Postmaxillectomy Prosthetic Rehabilitation in a Child: A Clinical Report. Issue 5 (3rd October 2016) - Elbashti, Mahmoud E.; Sumita, Yuka I.; Aswehlee, Amel M.; Haraguchi, Mihoko; Otomaru, Takafumi; Hattori, Mariko; Taniguchi, Hisashi
Abstract: This report describes the postmaxillectomy prosthetic rehabilitation of a child with maxillary chondrosarcoma over an 8‐year period. Specifically, it (1) describes the planning and rehabilitation procedures carried out during the period from before the operation to the time when the patient started elementary school and (2) reports the results of evaluations of the patient's oral and psychosocial function conducted during the school phase. The prosthetic treatment plan was separated into two phases (the preschool and school phases) and was started prior to surgery, when an immediate surgical obturator was designed by the surgeons. After the operation, it was considered important to provide the patient and her mother with training regarding how the defect should be cleaned, trismus prevention, and how the prosthesis should be fitted. In addition, esthetic improvements and the ability to speak clearly were also targeted during treatment planning. After surgery, obturators were fabricated in a conventional manner and fitted at the ages of 2, 4, 6, 8, and 10 years. The patient's oral function during the use of the obturators was evaluated objectively. Marked improvements in oral function were seen during both treatment phases. The patient's ability to perform psychosocial functions at school also improved during the use of the obturators.